Mechanical analysis of the roundhouse kick according to the stance position. A pilot study - Estevan, I.; Falcó, C.; Jandacka, D. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
In taekwondo combats, kick performance can be affected by the stance position. The aim of this study was to analyze mechanical variables in the roundhouse kick in taekwondo according to three stance positions (0º, 45º, 90º). Two high-level athletes participated in the study. Mechanical analysis was measured by two 3-D force plates and an eight-camera motion capture system. Data analyses were processed using Visual 3D software. From the 0º and 45º stance positions athletes kicked in less execution time and total response time than from the 90º stance position (p < 0.05). Moreover, the GRF predicted a high percentage of the variance of performance. Finally, the 0º and 45º stance positions seem more appropiate than the 90º stance position.